Natural T-cell ligands that are created by genetic variants can be transferred between cells by extracellular vesicles - Kremer, Anita; Zonneveld, Marijke I.; Kremer, Andreas E.; Van Der Meijden, Edith D.; Falkenburg, J. H. Frederik; Wauben, Marca H. M.; Nolte-'T Hoen, Esther N. M.; Griffioen, Marieke (European Journal of Immunology, 2018)
CD4 T-cells play a central role as helper cells in adaptive immunity. Presentation of exogenous antigens in MHC class II by professional antigen-presenting cells is a crucial step in induction of specific CD4 T-cells in adaptive immune responses. For efficient induction of immunity against intracellular threats such as viruses or malignant transformations, antigens from HLA class II-negative infected or transformed cells need to be transferred to surrounding antigen-presenting cells to allow efficient priming of naive CD4 T-cells. Here we show indirect antigen presentation for a subset of natural HLA class II ligands that are created by genetic variants and demonstrated that (neo)antigens can be transferred between cells by extracellular vesicles. Intercellular transfer by extracellular vesicles was not dependent on the T-cell epitope, but rather on characteristics of the full-length protein. This mechanism of (neo)antigen transfer from HLA class II-negative cells to surrounding antigen-presenting cells may play a crucial role in induction of anti-tumor immunity. This article is protected by copyright. All rights reserved.
EVALuna2:34446